Preparation of al/al203 and al/al203/ti02 photocatalysts for methyl tert-butyl ether degradation in aqueous phase under uv light irradiation / Zul Adlan Mohd Hir and Rusmidah Ali - Mohd Hir, Zul Adlan; Ali, Rusmidah (Universiti Teknologi MARA Cawangan Pahang, 2020)
Pollution of surface and groundwater by methyl tert-butyl ether (MTBE) is a serious world concern with respect to environment and human health. Human contact with MTBE has caused various ill-health problems such as fever, dizziness, cough, muscular aches, and irritation to the skin and eyes. Therefore, steps should be taken to reduce or totally eliminate the presence of such compounds in water. In this study, two types of photocatalysts, Al/Al2O3 and Al/Al2O3/TiO2 were tested in batch reactor system for the removal of MTBE in aqueous phase assisted by UV irradiation. The photocatalysts were prepared by anodic oxidation of Al plate in 0.4 M NaOH electrolyte solution. TiO2 was deposited onto the surface of Al/Al2O3 plate by electrolysis in an electrolyte solution containing a mixture of ammonium titanyl oxalate monohydrate, (NH4)2[TiO(C2O4)2].H2O and hydrated oxalic acid, (COOH)2.2H2O. The results indicate that the percentage of MTBE degradation using Al/Al2O3/UV and Al/Al2O3/TiO2/UV systems reached 89.35 % and 95.27 %, respectively. The effects of hydrogen peroxide (H2O2) and initial pH of MTBE aqueous phase were also studied using Al/Al2O3 photocatalyst. In both systems, MTBE degradation decreased to 82.57 % in the presence of H2O2. While the optimum pH was found to be the original pH of the sample solution (pH 7.75). This study demonstrated that Al/Al2O3/TiO2/UV system exhibited enhanced photoactivity, promoted better charge separation for degradation of organic pollutant in aqueous phase.